2017
DOI: 10.1002/asia.201701107
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Microporous Polymers for Heterogeneous Catalysis

Abstract: Conjugated microporous polymers (CMPs) are a class of crosslinked polymers that combine permanent micropores with p-conjugated skeletons and possess three-dimensional (3D) networks. Compared with conventionalm aterials such as metal-organic frameworks (MOFs) and covalent organic frameworks (COFs), CMPs usually have superior chemical and thermals tability.C MPs have made significant progress in heterogeneous catalysis in the past seven years. With ab ottom-up strategy,c atalytic moietiesc an be directly introdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(68 citation statements)
references
References 76 publications
0
68
0
Order By: Relevance
“…The development of heterogeneous catalysts with permanent and well‐defined porosity is one of the main goals of research in the field of catalysis. The Porous Polymer Catalysts, PPCs, represent a new, interesting and promising subclass of such heterogeneous catalysts . The PPCs are insoluble and non‐swellable polymers containing permanent pores in the size range of micropores and in some cases also mesopores and the catalytically active centers as the part of the micro/mesoporous surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of heterogeneous catalysts with permanent and well‐defined porosity is one of the main goals of research in the field of catalysis. The Porous Polymer Catalysts, PPCs, represent a new, interesting and promising subclass of such heterogeneous catalysts . The PPCs are insoluble and non‐swellable polymers containing permanent pores in the size range of micropores and in some cases also mesopores and the catalytically active centers as the part of the micro/mesoporous surface.…”
Section: Introductionmentioning
confidence: 99%
“…The Porous Polymer Catalysts, PPCs, represent a new, interesting and promising subclass of such heterogeneous catalysts. [1][2][3][4][5][6][7][8] The PPCs are insoluble and nonswellable polymers containing permanent pores in the size range of micropores and in some cases also mesopores and the catalytically active centers as the part of the micro/mesoporous surface. In terms of polymer architecture, the PPCs are highly aromatic polymer networks the permanent porosity of which results from the rigidity of the network segments and extensive cross-linking.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research advances have demonstrated that POPs are one type of promising materials as sulfur hosts, interlayers, and separators. However, to our best knowledge, the reviews for POPs are mainly focused on gas storage and separation, sensor, proton conductivity, drug delivery, and heterogeneous catalysis, POPs applications in Li–S batteries have not been systematically summarized hitherto.…”
Section: Introductionmentioning
confidence: 99%
“…[17] Thus, microporous polymers are good candidates fort he fabrication of high-activity catalysts, including MOFs, [11a, 18] covalent organic frameworks (COFs), [19] polymers of intrinsic microporosity (PIMs), [20] hyper-crosslinked polymers (HCPs), [21] and conjugated microporous polymers (CMP). [22] Among them, PIMs are distinguished for their easy processability.L inear PIMs are soluble in some organic solvents and usually have modifiable end groups.P IM-1 is at ypical PIM with nitrile groups on thep olymer backbone. The pendant nitrile groups can be converted into carboxyl groups by one-step hydrolysis in basic solution.…”
Section: Introductionmentioning
confidence: 99%